Yahoo! connected life - Isaacs, Andrew M.; Maclaurin, Angus; Taylor, Andrew (London : SAGE Publications Ltd, 2017)
Yahoo! felt it needed to establish a brand presence beyond the PC and the Web browser, and move onto the platform that still dominated information and entertainment for most Americans: the television. Yahoo! called it the "digital living room," but had yet to decide exactly what that meant or how they would go forward. The initiative had to include creating an interactive, on-demand, Yahoo!-branded channel for television. The management team needed to decide which customers would be attracted to content that Yahoo! Could deliver, and thus return to the Yahoo! Channel regularly. Although the move to TV was a strategic choice in order to gain relevance in the digital living room, Yahoo! was not willing to take a financial loss on the initiative just to gain a foothold in the world of television-based entertainment. In order to make such a Yahoo! TV channel effective, the team needed to work within the limitations of current television technology, as well as find a way to differentiate itself from the clutter of hundreds of other TV channels.
Originally published: Isaacs, A. M., Maclaurin, A., & Taylor, A. (2006).Yahoo! Connected Life. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Yahoo! Inc; Business planning; New products; Marketing; Television broadcasting